PENGARUH FAMILY SUPPORTIVE SUPERVISION TERHADAP WORK FAMILY BALANCE DAN ORGANIZATIONAL CITIZINSHIP BEHAVIOR (OCB) DI TEMPAT KERJA PADA BANK WILAYAH PEKANBARU - Suryatunnisak, Suryatunnisak; Handoyo, Leonardus Teguh; Hsb, Mhd. Suleman (Komunitas Manajemen Kompetitif, 2024)
This research aims to analyze the influence of family supportive supervision on work family balance and organizational citizenship behavior (OCB) in the workplace at banks in the Pekanbaru area. Where this research was conducted in banking in the Pekanbaru area. The data source for this research is banking employees throughout Pekanbaru, Riau. Indonesia. With a total of 101 respondents as the research sample. Furthermore, data analysis techniques include descriptive analysis, convergent and discriminant validity tests and reliability tests, as well as SEM-PLS analysis. Research results: from data that has been processed. Shows the calculation of the influence of the Family Supportive Supervision variable which has a positive effect on Work Family Balance, Family Supportive Supervision has no effect on Organizational Citizinship Behavior (Ocb), Work Family Balance has a positive effect on Organizational Citizinship Behavior (Ocb), Family Supportive Supervision has an effect on Work Family Balance and Organizational Citizenship Behavior (OCB). Keywords : Family Supportive Supervision, Organizational Citizinship Behavior (OCB), Work Family Balances